Chemotherapy-induced acute reversible toxic leukoencephalopathy - A K Vishnu; Thara Pratap; Dhanya Jacob; Muhammed Jasim Abdul Jalal; Anupama Gopalakrishnabhakthan (Current Medical Issues, 2022)
Acute toxic leukoencephalopathy can be due to a variety of endogenous and exogenous agents. Chemotherapy-induced toxic leukoencephalopathy is often encountered in clinical practice with the widespread use of various chemotherapeutic agents. Since initial clinical findings may be nonspecific, magnetic resonance imaging can be useful in the pattern recognition of white matter injury as well as to rule out its close differentials. Early diagnosis is important since prompt removal of the inciting agent and supportive therapy can reverse this condition, while delay can result in a poor prognosis. Here, we report a case of chemotherapy-induced toxic leukoencephalopathy in a patient with metastatic adenocarcinoma of the rectum from an imaging perspective.